รูปแบบการพัฒนาภาวะผู้นำเชิงกลยุทธ์สำหรับผู้บริหารโรงเรียนมัธยมศึกษา - กล้าศักดิ์ จิตต์สงวน (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
This research is the Descriptive Research and the objectives are; 1) to study the current and expected states 0f the strategic leadership performance of the secondary school administrators and, 2) to develop a model to improve the strategic leadership performance of the secondary school administrators. The subject of the study comprised four steps. The samples are the directors of the secondary schools who are under the Office Basic Education Commission 2,362 persons. The size of the samples is 340 persons from five regions and divided according to the size of the schools. The samples are 1,059 persons, 80.54 percentage. This includes 1) 36 Educational Service Area persons. 2) 255 school directors 3) 254 assistant directors 4) 257 the head of Educational Department 5) 257 the Chairman of School Board. The tools for research include questionnaires And evaluation paper for the suitable and probability. The collected data were analyzed by frequency distribution, percentage, mean, standard deviation and priority needs index.The research result can summarize as follows : The current state of strategic leadership performance of secondary school administrators was performed at a high level as a whole and while considering separately, all were performed at a high level as respectively ; Strategy creation with various imaginations. The current state of strategic leadership performance of secondary school administrators is in the high level like the Determined Vision. The Revolutionary Thinking is the highest need.A model of strategic leadership development for secondary school administrators is the form of conscious changing and build up the strategy for changing. This model is valid and the possibility of implement is at the highest level.